2014
DOI: 10.1007/s10935-014-0357-0
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Risk for Significant Behavior Problems Through a Cognitive-Behavioral Intervention: Effects of the Tools for Getting Along Curriculum at One-Year Follow-Up

Abstract: Efficient and effective social-emotional learning programs increase the likelihood of success in school for all students, and particularly for those who may develop emotional or behavior problems. In this study, we followed a sub-sample of students 1 year after their participation in a randomized controlled trial of the effects of the Tools for Getting Along (TFGA) curriculum. TFGA is a universally delivered, preventive cognitive-behavioral curricular intervention designed to improve upper elementary school st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Although no current available school‐based prevention or intervention simultaneously targets perceived stress, EF, and stress regulation, researchers have found that direct training and specific school‐based programs have shown promising results for improving self‐regulation and EF abilities (Crone, ; Diamond, ; Diamond & Lee, ). Though the evidence is less supportive for the transfer and maintenance of EF skills through direct computerized training, school‐based programs have demonstrated positive EF outcomes across grade levels: Tools of the Mind (Blair & Raver, ), Chicago School Readiness Project (Raver et al, ), Promoting Alternative Thinking Strategies (Riggs, Greenberg, Kusché, & Pentz, ), and Tools for Getting Along (Smith et al, ). Importantly, Smith et al () recently piloted an intensive intervention ( I Control ) for middle school students with EBD that explicitly taught and targeted self‐regulation (including goal setting, emotion regulation, and social problem solving) and EF, and they discovered positive gains for those students most in need of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Although no current available school‐based prevention or intervention simultaneously targets perceived stress, EF, and stress regulation, researchers have found that direct training and specific school‐based programs have shown promising results for improving self‐regulation and EF abilities (Crone, ; Diamond, ; Diamond & Lee, ). Though the evidence is less supportive for the transfer and maintenance of EF skills through direct computerized training, school‐based programs have demonstrated positive EF outcomes across grade levels: Tools of the Mind (Blair & Raver, ), Chicago School Readiness Project (Raver et al, ), Promoting Alternative Thinking Strategies (Riggs, Greenberg, Kusché, & Pentz, ), and Tools for Getting Along (Smith et al, ). Importantly, Smith et al () recently piloted an intensive intervention ( I Control ) for middle school students with EBD that explicitly taught and targeted self‐regulation (including goal setting, emotion regulation, and social problem solving) and EF, and they discovered positive gains for those students most in need of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Schoolwide and in-class universal social–emotional learning programs have demonstrated positive effects (Durlak, Weissberg, Dymnicki, Taylor, & Schellinger, 2011); although no studies have yet tested the effects of these programs on EF maturation, they are associated with positive outcomes (e.g., improved school safety) that are related to EF maturation. Additionally, school-based programs have shown promising results for improving EF abilities across grade levels (e.g., Tools of the Mind [Blair & Raver, 2014], Tools for Getting Along [Smith et al, 2014]); as such, these kinds of programs could be good investments for schools. Future research should continue to evaluate effectiveness of programs that address school-based stress and student EF.…”
Section: Discussionmentioning
confidence: 99%
“… Note . SPS = social problem solving; SIP = social information processing; beh = behavior; gr = grade; obs = observations; Em Reg = emotion regulation; Peer Acc = peer acceptance; RA = random assignment; M = male; EBD = students with emotional and behavioral disorders; Y = yes; N = no; TR = teacher report on student behaviors; SR = student self-report; Peer = peer nomination. a Fraser et al (2011) is a 6-month follow-up study of Fraser et al (2005), and Smith et al (2014) is a 1-year follow-up study of Daunic et al (2012). …”
Section: Resultsmentioning
confidence: 99%
“… a Fraser et al (2011) is a 6-month follow-up study of Fraser et al (2005), and Smith et al (2014) is a 1-year follow-up study of Daunic et al (2012). …”
Section: Resultsmentioning
confidence: 99%